Strategi Pengawas dalam Meningkatkan Etos Kerja Guru dan Tenaga Kependidikan - Yasiman (Yayasan Insanulhaq, 2024)
The quality of education in schools is greatly influenced by the role of professional supervisors, who are responsible for implementing educational guidance in order to create quality educational processes and outcomes. As teachers with additional duties as supervisors, as regulated in Permendiknas Number 13 of 2007, supervisors play an important role in supervision aimed at building and improving the quality of education. This study aims to measure the impact of guidance by supervisors on the work ethic of teachers and employees/administrators at MTsN 14 Ciamis, with a focus on three main aspects: the influence on improving teacher work ethic, the influence on employees/administrators, and the overall influence on the work ethic of both. Data were collected through observation, field notes, and reviews, and analyzed using qualitative descriptive methods with investigator triangulation to ensure the validity of the data. The results showed a significant increase in relevant activities of teachers and employees/administrators, with openness in sharing opinions increasing from 70.47% to 86.55% in the third cycle. Conversely, less relevant activities decreased, with scores dropping from 32.87% in the first cycle to 9.25% in the third cycle. Positive responses to coaching activities also increased, from 66.93% in the first cycle to 82.31% in the third cycle.